PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP SUSTAINABILITY REPORTING (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Annisa Sekar Pramesti Indah; Nur Cahyonowati (Diponegoro Journal of Accounting, 2023)
The challenges faced in moving forward and achieving sustainable development goals have made sustainability reporting an increasingly relevant topic in business and academia across the world, including Indonesia especially about its participation in issuing the Financial Services Authority Regulation (POJK) Number 51/POJK.03/2017 concerning the Implementation Sustainable Finance for Financial Service Institutions, Issuers, and Public Companies. This study aims to examine and find empirical evidence regarding the influence of corporate governance mechanisms on sustainability reporting according to the perspectives of both agency theory and resource dependence theory.The population in this study is all non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The purposive judgment sampling technique was employed to obtain 73 companies, yielding a total sampel of 219 firm-year observations over three years. Multiple regression analysis was selected as the method of analysis to test the hypothesis.The present study indicates that board of commissioners’ activity, board of commissioners’ training, and external audit quality have a positive influence on sustainability reporting. The other findings suggest that board of commissioners’ experience has a negative influence on sustainability reporting. Nevertheless, this study failed to find any influence of both board of commissioners’ independence and board of commissioners’ size on sustainability reporting.